If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = 2f + 4 Reorder the terms: 10 = 4 + 2f Solving 10 = 4 + 2f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-2f' to each side of the equation. 10 + -2f = 4 + 2f + -2f Combine like terms: 2f + -2f = 0 10 + -2f = 4 + 0 10 + -2f = 4 Add '-10' to each side of the equation. 10 + -10 + -2f = 4 + -10 Combine like terms: 10 + -10 = 0 0 + -2f = 4 + -10 -2f = 4 + -10 Combine like terms: 4 + -10 = -6 -2f = -6 Divide each side by '-2'. f = 3 Simplifying f = 3
| -26=-8(5-x)+2(-4+7x) | | 3x+6=-18+9x | | -10+5k=2k+3+5 | | 98+4= | | 2.9q-3.8-5.7=-3.8q-1.1 | | -5t+4t^2+5t-20= | | 5x+y=p^2-px | | 0+13y=21 | | 98x+x+3= | | (8x+2)=3x | | 2cos^2(x)+6=7 | | x^2+9y=7 | | X+(x+15)=3x-70 | | x*logx=24000000 | | -5n+n=-12-n | | 15x^5-9x^4=35x-21 | | 8-6d=34 | | 4x^2+4y^2-32x-4y+45=0 | | -4(4x+6)-8(x+7)=-32 | | 1.25+0.75m=10.25t | | 4z+16=3z+5 | | y=-0.35x^2+32.91x+5901.49 | | 2x+3y=4.5 | | 50x^14y^11z^2= | | 2(7X+4)=4X-6(2-Z)+7 | | -22-11=6a | | -17d+19=-3(6d-2)+1 | | 1/6+1/3= | | 8x+2=3x | | y^2-3x-28=0 | | -4v+8v=4v | | .4x-.5=.3x+6 |